2013
DOI: 10.1103/physrevd.88.074007
|View full text |Cite
|
Sign up to set email alerts
|

Baryonia and near-threshold enhancements

Abstract: The baryon-antibaryon spectrum consisting of strange, charm and bottom quarks is studied in the color flux-tube model with a multi-body confinement interaction. Numerical results indicate that many low-spin baryon-antibaryon states can form compact hexaquark states and are stable against the decay into a baryon and an antibaryon. The multi-body confinement interaction as a binding mechanism plays an important role in the formation of the states. They can be searched in the $e^+e^-$ annihilation and charmonium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…The color flux-tube structure of an ordinary hadron (qq meson or q 3 baryon) is unique and trivial, the multibody quadratic confinement potential is equivalent to the sum of two-body interactions in the color flux-tube model [17]. In this sense, the color flux-tube model is reduced to the traditional quark model and is therefore not a new model for ordinary hadrons.…”
Section: Color Flux-tube Model and Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The color flux-tube structure of an ordinary hadron (qq meson or q 3 baryon) is unique and trivial, the multibody quadratic confinement potential is equivalent to the sum of two-body interactions in the color flux-tube model [17]. In this sense, the color flux-tube model is reduced to the traditional quark model and is therefore not a new model for ordinary hadrons.…”
Section: Color Flux-tube Model and Hamiltonianmentioning
confidence: 99%
“…In the model, the color confinement used is not the sum of two-body interaction proportional to a color charge λ c i · λ c j but a multibody one, which has been successfully applied to study multiquark systems [14][15][16][17][18]. The study attempts not only to describe the reported charged states and to enrich the list of the possible charged states, but also to provide a new insight to charged states and to reveal the underlying mechanism behind these novel phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account information about production and decays of the Y(4260) state [7], φ(2170) might be its strange partner. Possible interpretations include a traditional ss state [8][9][10][11], hybrid state [8,12], tetraquark state [13][14][15], ΛΛ( 3 S 1 ) bound state [4,16], and φKK resonance state [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The internal constituents of the φ(2170) are still unknown, which has stimulated extensive theoretical discussions. Possible interpretations of the φ(2170) include a conventional 3 3 S 1 or 2 3 D 1 ss state [8][9][10][11], an ssg hybrid [9,12,13], a tetraquark state [14][15][16][17], a ΛΛ( 3 S 1 ) bound state [18][19][20], or a φKK resonance state [21], etc., but no interpretation has yet been established. Each of these theoretical models can accommodate a resonant state with parameters similar to those of the φ(2170), but they predict significantly different partial widths for individual decay modes, especially the K ( * ) K ( * ) decay modes, where the K ( * ) is the ground or excited state of a K meson with different spin-parities.…”
mentioning
confidence: 99%